Factors that predict deep inferior epigastric perforator flap donor site hernia and bulge. Issue 6 (2nd November 2018) - Butler, Daniel P.; Plonczak, Agata M.; Reissis, Dimitris; Henry, Francis P.; Hunter, Judith E.; Wood, Simon H.; Jallali, Navid
Abstract: Deep inferior epigastric artery perforator (DIEP) flap has become the gold standard in autologous breast reconstruction. Attention is now being focused on the impact of DIEP flap harvest technique on abdominal hernia rates. The aim of this study was to evaluate DIEP abdominal wall morbidity in relation to flap harvest and fascial closure technique. A retrospective analysis of patients undergoing DIEP flap breast reconstruction between 2012 and 2016 was performed. Post-operative evaluation of the abdominal wall integrity was performed by an operating consultant. The rectus fascia was closed using one of three techniques. The study included 202 patients, in whom 234 DIEP flaps were performed. Eight patients (3.4%) developed a clinically evident abdominal bulge post-operatively and one (0.5%) had a hernia. Harvesting two or more perforators was more likely to result in post-operative abdominal hernia/bulge than taking a single perforator ( p  = .032). Using a perforator from the lateral row or both rows was more likely to result in a hernia/bulge than if a single medial perforator was harvested ( p  = .026). Comparison of the rectus fascia closure technique did not show any statistically significant difference in abdominal wall morbidity. Consideration should be given towards perforator selection when harvesting a DIEP flap. Where appropriate, a suitable single medial row perforator with a favourable suprafascial course should be chosen. This study has not shown mesh-free fascial closure to be inferior to mesh-supported closure. Careful consideration to the role of synthetic mesh within this patient cohort should be given.